2013
DOI: 10.1071/wf11142
|View full text |Cite
|
Sign up to set email alerts
|

Effect of land-cover change on Africa's burnt area

Abstract: Abstract. The increasing global concern about wildfires, mostly caused by people, has triggered the development of human-caused fire occurrence models in many countries. The premise is that better knowledge of the underlying factors is critical for many fire management purposes, such as operational decision-making in suppression and strategic prevention planning, or guidance on forest and land-use policies. However, the explanatory and predictive capacity of fire occurrence models is not yet widely applied to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 170 publications
(154 reference statements)
4
22
0
2
Order By: Relevance
“…Indeed, as Caillait's [49] research found, burning is inversely related to population density-as population density increases, the area burned decreases. Others find similar results in other African regions [12,51]. It should be noted that agricultural density (population density) is not particularly high in either the Bougouni or Siby study areas and it is probable that fire regimes change only once a threshold of agricultural density is surpassed.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…Indeed, as Caillait's [49] research found, burning is inversely related to population density-as population density increases, the area burned decreases. Others find similar results in other African regions [12,51]. It should be noted that agricultural density (population density) is not particularly high in either the Bougouni or Siby study areas and it is probable that fire regimes change only once a threshold of agricultural density is surpassed.…”
Section: Discussionsupporting
confidence: 51%
“…The African savannas, which are the Earth's most extensively and frequently burned regions [11], account for some 64% of the global extent of area burnt annually [12]. Indeed, African savanna fires regularly burn such large areas that they are easily visible from space, so much so that NASA scientists refer to Africa as the "burn center of the planet" [13].…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…235 In Africa, land-use change within savanna regions has led to a reduction in burnt area of 8x10 5 ha year -1 , equivalent to 0.4% of area burned. 236 In regions of high fire risk, forest management and prescribed burns are used to reduce wildfire. 237 Prescribed burning involves the use of controlled fires to reduce surface fuel loads and the potential for future large and uncontrollable wildfires.…”
Section: -224mentioning
confidence: 99%
“…Due to the large scale at which biomass burning occurs, inter-annual variability in landscape fires is directly related to (greenhouse) gas concentrations in the atmosphere (Langenfelds et al, 2002) and affects regional air quality (Aouizerats et al, 2015;Crutzen et al, 1979;Langmann et al, 2009;Turquety et al, 2009). Fire regimes and fire management vary widely across (sub)tropical regions (Archibald et al, 2013), while ongoing socio-economic developments are expected to increasingly affect landscape fires and vegetation patterns during the coming century Chen et al, 2013;Grégoire et al, 2013). Fuel consumption per unit area burned (kg m −2 ), hereafter called fuel consumption for brevity, is a key indicator of the consequences of changing management practices, vegetation characteristics and climate on fire regimes, as well as a key parameter required in fire emission estimates.…”
Section: Introductionmentioning
confidence: 99%